Language development beyond the here-and-now: iconicity and displacement in child-directed communication - Motamedi, Y; Murgiano, M; Grzyb, B; Gu, Y; Kewenig, V; Brieke, R; Donnellan, E; Marshall, C; Wonnacott, E; Perniss, P; Vigliocco, G (Society for Research in Child Development, 2024)
Most language use is displaced, referring to past, future, or hypothetical events, posing the challenge of how children learn what words refer to when the referent is not physically available. One possibility is that iconic cues that imagistically evoke properties of absent referents support learning when referents are displaced. In an audio-visual corpus of caregiver–child dyads, English-speaking caregivers interacted with their children (N = 71, 24–58 months) in contexts in which the objects talked about were either familiar or unfamiliar to the child, and either physically present or displaced. The analysis of the range of vocal, manual, and looking behaviors caregivers produced suggests that caregivers used iconic cues especially in displaced contexts and for unfamiliar objects, using other cues when objects were present.